Development of a method for selected financing of scientific and educational institutions through targeted capital investment in the development of innovative technologies - Levchenko, Iaroslava; Dmytriieva, Oksana; Shevchenko, Inna; Britchenko, Igor; Kruhlov, Vitalii; Avanesova, Nina; Kudriavtseva, Oksana; Solodovnik, Olesia (Технологічний центр, 2021)
The problem of supporting scientific and educational institutions is considered. A method of selective financing of scientific and educational institutions that create innovative technologies taking into account their investment in innovative developments is proposed. On the basis of statistical data on the indicators for assessing the activities of scientific and educational institutions and the indicator of the innovative potential of a scientific and educational institution from the production of innovations (PNn), their rating was calculated. The essence of PNn is to compare the indicators of the volumes of income of the special fund Dsfn and the volume of expenditures of the scientific and educational institution Vn. In order to stimulate scientific and educational institutions to create innovative technologies, it was proposed to introduce targeted investments. The problem of quantifying the rate of premium on the basis of an integrated approach in terms of indicators of innovative potential from the production of innovations and the rating of a scientific and educational institution for 2 institutions (namely: K and H) has been solved. Institution K will receive a large increase, and institution N will receive a smaller increase, the value of which will be 56.23 % and 43.76 %, respectively. The results showed the independence of the indicator of the innovative potential of a scientific and educational institution from the production of innovations from the previous rating of a scientific and educational institution, or vice versa. The proposed methodology has been tested by an experimental method, targeted investments have been determined based on an integrated approach in terms of indicators of innovative potential and the rating of a scientific and educational institution. This study is of practical interest to government authorities and grantors when allocating funds according to the vector of selective financing of scientific and educational institutions through targeted investments in the development of innovative technologies, and theoretically – to researchers dealing with issues of financial security, protectionism and public administration.
Keywords: scientific and educational institution; allowance; innovative technologies; selective financing; targeted investment; rating